Simultaneous quantification of direct oral anticoagulants currently used in anticoagulation therapy - Foerster, Kathrin; Huppertz, Andrea; Müller, Oliver J.; Rizos, Timolaos; Tilemann, Lisa; Haefeli, Walter E.; Burhenne, Jürgen (Journal of pharmaceutical and biomedical analysis, 2018)
Direct oral anticoagulants (DOACs) are among the most effective options to prevent serious thromboembolic events in patients with atrial fibrillation. Coagulation assays are used to assess DOAC activity, but lack the possibility to quantify drugs with concurrent pharmacodynamic effect. We developed a selective multi-drug assay to analyze apixaban, betrixaban, dabigatran, edoxaban, edoxaban M4, and rivaroxaban with ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC/MS/MS) in plasma fulfilling all requirements of the FDA und EMA guidelines for bioanalytical method validation. Plasma samples were extracted using solid phase extraction in a 96-well micro volume format. Chromatographic separation was performed on a Waters BEH Phenyl 1.7μm column coupled to tandem mass spectrometry. Extraction recoveries exceeded 80 %. Concentrations of 1-1000 ng/ml can be precisely quantified (correlation coefficient of >0.99) using 100 μL plasma volume. Intra-day and inter-day accuracies ranged between 91.0 % and 116 %. Precisions at low and high concentrations were below 13.3 %. The method was applied within a clinical drug trial and eight short pharmacokinetic profiles of patients under DOAC therapy were analyzed. The assay allows for highly sensitive and selective simultaneous quantification of DOACs in patient plasma samples.
Available online: 16 October 2017
Gesehen am 10.04.2018